THE INFLUENCE OF OCCUPATIONAL HEALTH AND SAFETY ON THE PERFORMANCE OF EMPLOYEES IN THE MANUFACTURING INDUSTRY - Donny Arif; Elsa Ajeng Panghestuningtyas; Mukti Ali (Ecopreneur.12, 2022)
This study aims to determine the effect of occupational safety and health in the Indonesian manufacturing industry using quantitative research. This sampling method uses a saturated sample: all samples of people are required to apply work safety and occupational health. The data analysis technique used was multiple regression which was processed using SPSS Version 21. Based on the results of data analysis, it was found that occupational health partially has a positive and significant effect on employee performance. At the same time, work safety does not influence employee performance. Thus it can be concluded that simultaneously or together, occupational safety and occupational health variables have a positive and significant effect on employee performance. The variables of occupational safety and occupational health together contribute to employee performance.